Curcumin reduces development of seizurelike events in the hippocampal‐entorhinal cortex slice culture model for epileptogenesis. (12th February 2019) - Drion, Cato M.; Kooijman, Lieneke; Aronica, Eleonora; van Vliet, Erwin A.; Wadman, Wytse J.; Chameau, Pascal; Gorter, Jan A.
Summary: Objective: Inhibition of the mammalian target of rapamycin (mTOR) pathway could be antiepileptogenic in temporal lobe epilepsy (TLE), possibly via anti‐inflammatory actions. We studied effects of the mTOR inhibitor rapamycin and the anti‐inflammatory compound curcumin—also reported to inhibit the mTOR pathway—on epileptogenesis and inflammation in an in vitro organotypic hippocampal‐entorhinal cortex slice culture model. Methods: Brain slices containing hippocampus and entorhinal cortex were obtained from 6‐day‐old rat pups and maintained in culture for up to 3 weeks. Rapamycin or curcumin was added to the culture medium from day 2 in vitro onward. Electrophysiological recordings revealed epileptiformlike activity that developed over 3 weeks. Results: In week 3, spontaneous seizurelike events (SLEs) could be detected using whole cell recordings from CA1 principal neurons. The percentage of recorded CA1 neurons displaying SLEs was lower in curcumin‐treated slice cultures compared to vehicle‐treated slices (25.8% vs 72.5%), whereas rapamycin did not reduce SLE occurrence significantly (52%). Western blot for phosphorylated‐S6 (pS6) and phosphorylated S6K confirmed that rapamycin inhibited the mTOR pathway, whereas curcumin only lowered pS6 expression at one phosphorylation site. Real‐time quantitative polymerase chain reaction results indicated a trend toward lower expression of inflammatory markers IL‐1β and IL‐6 and transforming growth factor β after 3 weeks of treatment with rapamycin and curcumin compared to vehicle. Significance: Our results show that curcumin suppresses SLEs in the combined hippocampal‐entorhinal cortex slice culture model and suggest that its antiepileptogenic effects should be further investigated in experimental models of TLE.